2021
DOI: 10.1186/s12935-021-02383-z
|View full text |Cite
|
Sign up to set email alerts
|

TKTL1 participated in malignant progression of cervical cancer cells via regulating AKT signal mediated PFKFB3 and thus regulating glycolysis

Abstract: Background Cervical cancer (CC) is the second most common cancer among women with high morbidity and mortality. TKTL1 is a key protein in glucose metabolism in cancer cells and controls the pentose phosphate pathway (PPP). In this paper, we aim to explore whether TKTL1 can participate in the malignant process of CC cells through glucose metabolism. Methods The expression and activity of TKTL1 in CC cell lines were detected by RT-qPCR and Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…This metabolic switch provides an advantageous supply of material and energy substrate for tumor cell growth, enabling them to survive hypoxic environments. Studies have shown that transketolase like 1 (TKTL1) accelerates the malignant process of CC cells by participating in glycolysis [21]. Myosin 1B (MYO1B) activates the extracellular regulated protein kinases (ERK)/HIF-1A pathway and its downstream glycolysis-related genes, promoting glycolysis, migration and invasion, thus promoting the malignant progression of CC [22].…”
Section: Discussionmentioning
confidence: 99%
“…This metabolic switch provides an advantageous supply of material and energy substrate for tumor cell growth, enabling them to survive hypoxic environments. Studies have shown that transketolase like 1 (TKTL1) accelerates the malignant process of CC cells by participating in glycolysis [21]. Myosin 1B (MYO1B) activates the extracellular regulated protein kinases (ERK)/HIF-1A pathway and its downstream glycolysis-related genes, promoting glycolysis, migration and invasion, thus promoting the malignant progression of CC [22].…”
Section: Discussionmentioning
confidence: 99%
“…Glycolysis has been associated with CC cell proliferation and apoptosis [ 43 , 44 ]. Interestingly, glycolysis was related to the expression of FAM83F [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This activation leads to increased glucose consumption, lactate secretion and ATP production. Inactivation of the Akt pathway by targeting these molecules could suppress the malignant process 49 , 50 . HR-HPV infection negatively regulates miR-155-5p expression while activating Akt/mTOR signaling to promote glycolytic flow.…”
Section: Glucose Metabolism In CCmentioning
confidence: 99%